Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/ijerph16050854
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean Built Environment and Precipitation as Modulator Factors on Physical Activity in Obese Mid-Age and Old-Age Adults with Metabolic Syndrome: Cross-Sectional Study

Abstract: When promoting physical activity (PA) participation, it is important to consider the plausible environmental determinants that may affect this practice. The impact of objectively-measured public open spaces (POS) and walk-friendly routes on objectively-measured and self-reported PA was explored alongside the influence of rainy conditions on this association, in a Mediterranean sample of overweight or obese senior adults with metabolic syndrome. Cross-sectional analyses were undertaken on 218 PREDIMED-Plus tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…On the other hand, while temperature does not seem to be playing a specific role among those who reside in high walkable environments, the presence of rain was significantly associated with lower walking levels among this second group of seniors. This is in line with Colom, Ruiz, Wärnberg, et al (2019), who found that rain especially had an effect on walkable routes in promoting outdoor physical activity among older adults [27]. These results could be explained, on the one hand, by the fact that sidewalks and pedestrian crossings (which are more present compared to low-walkable neighborhoods) are especially slippery and might present puddles in rain conditions and therefore, fear of falling among seniors could be especially aggravated [38,39].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…On the other hand, while temperature does not seem to be playing a specific role among those who reside in high walkable environments, the presence of rain was significantly associated with lower walking levels among this second group of seniors. This is in line with Colom, Ruiz, Wärnberg, et al (2019), who found that rain especially had an effect on walkable routes in promoting outdoor physical activity among older adults [27]. These results could be explained, on the one hand, by the fact that sidewalks and pedestrian crossings (which are more present compared to low-walkable neighborhoods) are especially slippery and might present puddles in rain conditions and therefore, fear of falling among seniors could be especially aggravated [38,39].…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, and in colder settings, Clarke et al (2017) found that under snow conditions, older adults who lived in very walkable neighborhoods walked to 25% fewer destinations [26]. Lastly, by analyzing a Mediterranean context, Colom et al (2019) found that while route walkability had an influence on accelerometer-measured physical activity, rainy conditions during the accelerometer wearing period modified this association [27].…”
Section: Introductionmentioning
confidence: 99%
“…Each of the three studies with a high risk of bias scored "high" for the domain of study attrition, due to inadequate response rates, 38 inadequate reasons provided for participant drop-out, 39 reported differences in participant characteristics between those who completed the study and those who did not, 38 or a lack of reporting on potential differences between those who completed the study and those who did not. 39,40 In assessing methodological quality, agreement between the two reviewers was fair (kappa = 0.29, 95% CI −0.07 to 0.65), with independent ratings and final consensus by domain recorded. The qualitative study 43 adequately described nine out of ten items in the CASP tool, but the relationship between researcher and participants was deemed to have not been adequately considered (Figure 3).…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Twenty-nine of 34 determinants were only evaluated in one quantitative study, therefore these were downgraded for inconsistency. Where there was an absence of rationale for sample sizes, [38][39][40] sample sizes were considered adequate; thus, no determinants were downgraded for imprecision. 34 No determinants were upgraded as there was no evidence of moderate or large effect sizes or exposure-response gradients.…”
Section: Determinants Of Adherence To Epamentioning
confidence: 99%
“…The outcome measures that were reported in the selected studies included a combination of physical activity level (Colom et al, 2019;Forte et al, 2019;Gell, Rosenberg, Carlson, Kerr, & Belza, 2015;Giehl, Hallal, Corseuil, Schneider, & d'Orsi, 2016;Hanibuchi, Kawachi, Nakaya, Hirai, & Kondo, 2011;Huang, Kung, & Hu, 2018;Janssen et al, 2014;Kolbe-Alexander, Pacheco, Tomaz, Karpul, & Lambert, 2015;Li, Fisher, Brownson, & Bosworth, 2005; Y. Lu, Chen, Yang, & Gou, 2018;Mazzei, Gillan, & Cloutier, 2014;Nagel, Carlson, Bosworth, & Michael, 2008;Parra, Gomez, Fleischer, & Pinzon, 2010;Rosbergen, Grimley, Hayward, & Brauer, 2019;Rosbergen et al, 2017;Sato, Inoue, Du, & Funk, 2019;Timmermans et al, 2016;Winters et al, 2015), falling rates (Campbell et al, 2005;Cumming et al, 1999;Day et al, 2002;Lannin et al, 2007;Nikolaus & Bach, 2003;Pardessus et al, 2002;Stevens, Holman, Bennett, & De Klerk, 2001) Engel et al, 2016;Lannin et al, 2007;Lin, Wolf, Hwang, Gong, & Chen, 2007;Nicholson, McKean, & Burkett, 2014;Pighills, Torgerson, Sheldon, Drummond, & Bland, 2011;Rosbergen et al, 2017), ADL (Lannin et al, 2007;Law, Barnett, Yau, & Gray, 2013;Law, Fong, & Yau, 2018;Liu, Jones, Formyduval, & Clark, 2016;…”
Section: Main Findingsmentioning
confidence: 99%